DETERMINING PRIORITIES FOR DEFENSE TECHNOLOGY DEVELOPMENT TO SUPPORT THE PROTECTION OF STRATEGIC VITAL AREAS OF THE INDONESIAN NAVY IN ORDER TO COUNTER MILITARY AND NON-MILITARY THREATS WITHIN THE TERRITORY OF THE REPUBLIC OF INDONESIA - Hendrik Kurniawan; Sri Depranoto; Adhi Windarko (AGUSPATI Research Institute, 2026)
— The development of modern defense technology has become a critical component of national security strategy in responding to increasingly complex and multidomain threats. This study examines the prioritization of defense technology development to support the protection of Strategic Vital Areas of the Indonesian Navy against both military and non-military threats. Using an integrated methodological approach, the study combines the Analytical Hierarchy Process (AHP) and SWOT analysis to generate objective and strategic recommendations. The AHP results indicate that cyber resilience is the highest priority, surpassing C-ISR and UAV technologies, highlighting its fundamental role in ensuring the effectiveness of modern network-centric defense systems. Without robust cyber capabilities, other defense technologies are vulnerable to disruption and degradation. Furthermore, the SWOT analysis positions the strategy within the W–O (turnaround) quadrant, emphasizing the need to leverage external opportunities to overcome internal limitations. The recommended strategies include developing an integrated cyber defense architecture, enhancing interoperability through international cooperation, strengthening domestic defense industry capabilities, and implementing layered cyber defense systems. Overall, this study underscores the importance of cyber resilience as the backbone of adaptive, integrated, and sustainable defense capabilities to safeguard national sovereignty in the era of asymmetric and hybrid threats.